The The relationship between tooth brushing habits and dental caries in third and fourth grade elementary school children: The Relationship Between Tooth Brushing Habits and Dental Caries - Yuli Yani Dwi Lestari; Istinengtiyas Tirta Suminar; Siti Arifah (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: Dental caries is one of the most common oral health problems among elementary school children and can affect their comfort, chewing ability, and learning activities. One behavioral factor suspected to play a role in the development of dental caries is tooth brushing habits. Purpose: This study aims to determine the relationship between tooth brushing habits and dental caries in elementary school children in grades 3-4 Method: This quantitative study used a descriptive correlational design and a cross-sectional approach. The sampling technique used purposive sampling, with a sample size of 58 respondents. Data on tooth brushing habits were collected using a questionnaire, while data on dental caries were obtained through direct observation. Data analysis was performed using univariate and bivariate analysis with the Chi-square test at a significance level of p<0.05. Results: The results showed that most respondents had good tooth brushing habits (63.8%), adequate habits (34.5%), and poor habits (1.7%), and the majority of children had dental caries with a frequency of 82.8%. The Chi-square test results showed a value of (p=0.839), meaning that P Value >0.05, which means that Ha is rejected and Ho is accepted, indicating that there is no significant relationship between tooth brushing habits and dental caries in children in grades 3-4 at SDN Nogotirto. Conclusion: There is no significant relationship between toothbrushing habits and dental caries in third and fourth grade elementary school children.